Synthetic Applications of Monofluoromethylsulfonium Salts - Melngaile, Renate; Veliks, Janis (Synthesis, 2021)
Monofluoromethylsulfonium salts are emerging reagents for the fluoromethylation and fluoromethylenation or fluoromethylene transfer. Using this type of reagent is a simple approach for the introduction of the fluoromethyl group into a wide range of nucleophiles using mild basic conditions. Recently, fluoromethylsulfonium salts have been demonstrated to act as a synthetic equivalent for the challenging fluoromethylene synthon. For instance, these reagents can be used for the direct synthesis of monofluoroepoxides and fluorocyclopropanes from activated alkenes via a sulfur fluoromethylide intermediate. Sulfonium salts are an alternative, easy-to-handle option to volatile and environmentally concerning freons for achieving monofluorinated compounds. This review focuses on synthetic application of these reagents known to date.1 Introduction2 Fluoromethylation of O-, N-, S-, P-, and C-Nucleophiles3 Sulfonium Salts for Radical Monofluoromethylation of Alkenes4 Sulfonium Salts for Fluoromethylene Transfer5 Conclusions
Keywords: fluoromethylation; fluoromethylenation; sulfur fluoromethylide; sulfonium salts; fluorocarbene; fluoromethylene transfer